Connectivity for Caribbean Countries : An Initial Assessment - Briceno-Garmendia, Cecilia (World Bank Group, Washington, DC, 2015)
Every discussion of the Caribbean states considers their characteristics as sea-locked countries, small economies, highly vulnerable to natural disasters, and a geographic platform that calls for regional cooperation and integration. The Caribbean Sea is the most important vehicle and the most challenging obstacle Caribbean countries have to connect with the world. This report measures and analyzes the Caribbean region's air and maritime connectivity, by taking a sample of 15 countries that represent 64 percent of the Caribbean population and 59 percent of the region's gross domestic product. The report finds that the most salient issue of Caribbean logistics is the huge costs associated with trade, driven by embedded inefficiencies in customs systems and document preparation processes. The report also documents how the Caribbean air transport network is characterized by fierce competition between the islands for tourists from abroad, rather than coordinated efforts to promote Caribbean tourism. This has led to suboptimal routing based on distorting subsidy schemes with often unstainable volumes and load factors, raising questions about the sustainability of many of the extra-Caribbean routes, and indicating a need for route consolidation. Air connectivity within and among Caribbean states is poor and represents an opportunity to develop alternative and more competitive private sector-led services such as inter-island ferries and low-cost air shuttle services. Maritime connectivity for freight is well structured around two coexisting and functional hub-and-spoke systems (intra-regional with a hub in Trinidad and extra-regional with a hub in the Miami area) that effectively serve all the Caribbean countries. Yet, tariffs are high by worldwide standards and are likely driven by high market concentration in a handful of shipping liners.